Fundamental Properties of Metal-Adsorbed Silicene: A DFT Study - Tran, Ngoc Thanh Thuy (ACS Omega, 2020)
[Image: see text] Sodium, magnesium, and aluminum adatoms, which possess one, two, and three valence electrons, respectively, in terms of 3s, 3s(2), and (3s(2), 3p) orbitals, are very suitable for helping us understand adsorption-induced diverse phenomena. In this work, the revealing properties of metal (Na/Mg/Al)-adsorbed graphene systems are investigated by means of the first-principles method. The single- and double-sided chemisorption cases, the various adatom concentrations, the hollow/top/valley/bridge sites, and the buckled structures are taken into account. The hollow and valley adsorptions that correspond to the Na/Mg and Al cases, respectively, create extremely nonuniform environments. This leads to diverse orbital hybridizations in Na/Mg/Al–Si bonds, as indicated by the Na/Mg/Al-dominated bands, as well as the spatial charge density distributions and the orbital-projected density of states (DOS). Out of three types of metal-adatom adsorptions, the Al-adsorption configurations produce the strongest chemical modifications. The ferromagnetic configurations have been shown to survive only in specific Mg and Al adsorptions, but not in the Na cases. The presented theoretical predictions could be verified experimentally, and potential applications are discussed. Additionally, important similarities and differences with graphene-related systems are examined.